Antigen-driven autoantibody production in lungs of interstitial lung disease with autoimmune disease. Issue 121 (July 2021) - Takeshita, Masaru; Suzuki, Katsuya; Nakazawa, Maho; Kamata, Hirofumi; Ishii, Makoto; Oyamada, Yoshitaka; Oshima, Hisaji; Takeuchi, Tsutomu
Abstract: Interstitial lung disease (ILD) sometimes becomes a life-threatening complication of systemic autoimmune diseases; however, little is known about the immune response in lung lesions. We aimed to investigate humoural immunity in ILD associated with rheumatoid arthritis (RA), sjögren's syndrome (SjS), and mixed connective tissue disease (MCTD), using bronchoalveolar fluid (BALF) and serum samples from 15 patients with autoimmune disease associated-ILD. We first showed that BALF contained higher titers of disease-related autoantibodies than serum, suggesting the possibility of autoantibody production in lungs. Next, we produced 326 monoclonal antibodies from antibody-secreting cells in BALF, and the reactivity and their revertants, in which somatic hypermutations were reverted to germline, were analyzed. Among 123 antibodies from RA-ILD, 16 disease-related antibodies (anti-modified protein antibodies and rheumatoid factors) were identified, of which one antibody had both properties. The revertant antibodies changed their target modification in a complicated manner, suggesting that the antibodies were selected against various modifications in lungs. Among 146 antibodies from SjS-ILD and/or MCTD-ILD, seven anti-SSA/Ro60 antibodies and 15 anti-RNP antibodies were identified. Some of the anti-RNP antibodies recognized multiple RNP constituent proteins simultaneously, indicating that epitope spreading may progress in lungs. Our results revealed the existence of an active autoimmunity in the lungs of autoimmune disease associated-ILD. Highlights: BALF contained higher titers of disease-related autoantibodies than serum. 6–24% of antibody-secreting cells in BALF produce disease-specific autoantibody. Autoantibodies are produced in lungs in an antigen-driven manner. AMPA produced in lungs have high plasticity of the target modifications. Anti-RNP antibodies may show cross-reactivity to RNP constituent proteins.